Awareness about organ donation among school girls - Saha, M; Hadiuzzaman, KM; Faroque, MO; Alam, KS; Haque, MA; Paul, BK (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Apr;20(2): 287-291 The abstract of this article is available on the PubMed website